2011
DOI: 10.1038/cdd.2011.190
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-128-2 targets the transcriptional repressor E2F5 enhancing mutant p53 gain of function

Abstract: p53 mutations have profound effects on non-small-cell lung cancer (NSCLC) resistance to chemotherapeutic treatments. Mutant p53 proteins are usually expressed at high levels in tumors, where they exert oncogenic functions. Here we show that p53R175H, a hotspot p53 mutant, induces microRNA (miRNA)-128-2 expression. Mutant p53 binds to the putative promoter of miR128-2 host gene, ARPP21, determining a concomitant induction of ARPP21 mRNA and miR-128-2. miR-128-2 expression in lung cancer cells inhibits apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
121
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(129 citation statements)
references
References 39 publications
8
121
0
Order By: Relevance
“…However, no significant effects on the expression levels of these four genes were detected upon miR-128-3p over-expression in T-ALL cell lines (Online Supplementary Figure S4), thus excluding miR-128-3p from broader interaction in the T-ALL regulatory network. Next, we also looked at other validated miR-128-3p target tumor suppressor genes in other tumor entities including BAX 13 and E2F5 14 (as well as SUZ 1215 and NF1…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant effects on the expression levels of these four genes were detected upon miR-128-3p over-expression in T-ALL cell lines (Online Supplementary Figure S4), thus excluding miR-128-3p from broader interaction in the T-ALL regulatory network. Next, we also looked at other validated miR-128-3p target tumor suppressor genes in other tumor entities including BAX 13 and E2F5 14 (as well as SUZ 1215 and NF1…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Donzelli and collaborators showed that miR-128-2 expression, induced by a mutant p53 protein, inhibits apoptosis and causes increased resistance to doxorubicin, cisplatin and 5-fluorouracil in NSCLC cells. MiR-128-2, by targeting E2F5, inhibits its repressive activity on transcription of p21 waf1 , which exerts an anti-apoptotic effect by reducing pro-caspase-3 cleavage [87]. Additionally, miR-330 expression was correlated with resistance to gemcitabine in various lung cancer cell lines, since gemcitabine-sensitive cells showed a lower expression of miR-330 than gemcitabine-resistant cells.…”
Section: Mirnas Involved In Chemoresistance Through Cell Cycle Regulamentioning
confidence: 99%
“…23 This results in the regulation of cell death 24 or cell cycle. [25][26][27] A relevant metabolic role of p53 is exerted during hypoxia, as oxygen relative pressure reaches particularly lower levels at the center of the tumors, where p53 protein interplays with mTOR 28 as well as with the more classic pathways of HIF-1a and VHL. 29 A distinct role occurs during re-oxygenation, as during miocardial infartion or trombosis in the central nervous system.…”
Section: Introductionmentioning
confidence: 99%